Durability Characteristics of Concrete and Reinforcing Bars Exposed to Harsh Environments - Sanaa Abdul Hadi Hafad; Farah Hamed Rashed (Engineering and Technology Journal, 2014)
Saline pollution attack is an important factor that leads to the deterioration of the concrete, especially in industrial plants. In spite of research address the sustainability of concrete and particularly steel rebar submeserged in it steel rebar is the most important causal factors the deterioration in the reinforced concrete the main aim of this research is study the effect of additives added to reduce superior degree water and two types of mineral additives that include silica fumes and steel fiber, as well as the combined effect of these additives on the properties of concrete. The experimental work of this measure include concrete specimens have been partially submerged in a solution of chlorides and sulfates in concentrations similar to those found in aggressive conditions. The properties of concrete specimens were evaluated through the properties investigated included ultrasonic plus velocity, compressive strength electrochemical potential for various types of mixes. Concrete mixed with 10% of silica shown development all properties of concrete, while these properties deceases values of mix reference coated with natural rubber (RFCNR) and steel fiber coated with natural rubber (STFCNR). The result coated specimens has shown resistance to corrosion greater than specimens without coated when immersion in salt solution. Thus group (RFCNR )shown more develops in all properties as compared with all other mixture immersed in salt solution for 180 days at odds with group ( SF-SP) which had development in all properties as compared with the reference mixture at 180 days of immersion in salt solution .